Thermal sensation between 1981-2019 in Lagoa Seca, Paraíba, Brazil (Research, Society and Development, 2020)
The objective is to analyze the temporal and punctual oscillations of the maximum and minimum thermal sensations and their level of discomfort, relating the climate variability and the urban conformation between 1981-2019, for Lagoa Seca - PB, as well as debating its possible causes and subsidizing information to researchers and decision makers in various areas of activity. The data of the maximum and minimum air temperatures were generated by the Estima_T software for the period 1981-2019, the relative humidity data (%) were generated using the simplified linear interpolation method of the municipalities that operate meteorological stations. In the analysis of the thermal comfort level of the studied area, for the maximum and minimum temperatures and the seasons. They used the bioclimatic index proposed by Thom (1959), most commonly used in urban climate studies, to describe the thermal sensation that a person experiences due to the climatic conditions of an environment. The analysis of climatic conditions will allow better planning and environmental management of urban and rural areas in the studied area. More than 50% of the population demonstrated that there is thermal discomfort, even though the municipal area has good vegetation coverage within the municipality and its surroundings and that these thermal discomforts are centered on some days in the months of November, December, January, February and July for maximum temperature, in March, July and August for minimum temperature.